Bacterial quorum sensing and the role of algae in bacterial diseases control in aquaculture - Wiyoto.; Ekasari, Julie (Jurnal Akuakultur Indonesia, 2010)
Bacterial disease is one of the most common diseases in aquaculture practices which have a significant impact. Several researches noted that pathogenicity of a certain bacteria can be determined by its quorum sensing activity. Quorum sensing is a communication process of a certain bacteria with the same or different species of bacteria which involves the releasing and capturing of signal molecule to and from the environment. This activity will activate a certain target gene which further resulted in the expression of a phenotype by the bacteria. With regard to this characteristic, one of the methods to control bacterial diseases is by quorum sensing disruption. Several species of algae, both micro and macro, have been found to be able to intervense bacterial quorum sensing and thus can be used as an alternative in bacterial disease control. Key words: quorum sensing, bacterial disease, aquaculture, algae Abstrak Penyakit bakteri adalah salah satu penyakit yang paling umum dalam akuakultur dengan dampak yang cukup signifikan. Beberapa penelitian menunjukkan bahwa tingkat patogenitas suatu bakteri salah satunya ditentukan oleh aktivitas kuorum sensing bakteri. Kuorum sensing bakteri merupakan suatu proses komunikasi yang dilakukan oleh bakteri dengan bakteri lainnya baik yang sejenis maupun berlainan jenis yang berupa pelepasan dan penangkapan molekul sinyal menuju dan dari lingkungan sekitar bakteri tersebut. Aktivitas inilah yang akan menentukan ekspresi suatu gen target seperti patogenitas, sehingga salah satu metode yang dapat digunakan dalam mengendalikan penyakit yang disebabkan oleh bakteri adalah dengan mengganggu aktivitas kuorum sensing bakteri. Beberapa jenis alga, baik mikro maupun makro, diketahui dapat mengintervensi aktivitas kuorum sensing, dan dapat menjadi salah satu alternatif bagi pengendalian penyakit bakterial. Kata-kata kunci: kuorum sensing, penyakit bakterial, akuakultur, alga